PERAN DAN IMPLIKASI KAPSEL DALAM PENEGAKAN HUKUM PIDANA - Okprianti, Reny; Emilson, Nur Husni; Ramadhania, Nailah; Nadira, Saffana; Anggraini, Adelia Oktarina; Freza, Windri (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2024)
This paper discusses the role and implications of implementing the capsule concept in criminal law enforcement in Indonesia. Capsule is a legal approach that provides flexibility in the application of criminal sanctions, with the aim of accommodating the principle of substantive justice by considering the specific conditions of each case that occurs. This approach provides an opportunity for law enforcement officers to consider mitigating factors, such as age, psychological condition, socio-economic background, and the motivation of the perpetrator, to ensure that the punishment imposed not only fulfills the retributive aspect but also reflects rehabilitative and preventive values. In its implementation, capsules contribute to reducing the density of correctional institutions, increasing the effectiveness of perpetrator rehabilitation, and strengthening public trust in the existing criminal law system. This approach also supports legal reform that is more adaptive and responsive to ongoing social dynamics. However, its implementation faces challenges, especially in terms of regulations that are still not specific and resistance from some people who still view severe punishment as the main form of justice. Thus, capsules play an important role in creating a balance between law enforcement and human rights protection, as well as encouraging a more humane renewal of the justice system.